Description of two new species of Psyllaephagus Ashmead (Hymenoptera: Encyrtidae) parasitizing Phacopteron lentiginosum Buckton (Hemiptera: Psyllidae), a leaf gall-former of Garuga pinnata Roxburgh (Burseraceae) - Singh, Sudhir; Singh, Karan Pal (Zootaxa, 2011)
Two new species of Encyrtidae, Psyllaephagus phacopteron sp. nov. and Psyllaephagus garuga sp. nov. (Hymenoptera: Chalcidoidea) from Dehradun, Uttarakhand, India, that parasitize Phacopteron lentiginosum Buckton (Hemiptera: Psyllidae), a leaf-galler of Garuga pinnata Roxburgh (Burseraceae), are described. The two species are differentiated from other known Indian species of the genus through modifying a previously published key to species.